The science and education of mechatronics engineering. - Wikander, J. (IEEE Robotics and automation magazine)
We try to get to the heart of multidisciplinary engineering, of which mechatronics is an excellent example, and point out how the integration of disciplines leads to new degrees of freedom in design and corresponding research directions that otherwise would not have been investigated. This is the major contribution achieved by a multidisciplinary approach to engineering science; it leads to a new important research field and at the same time helps to push research in related fields into new fruitful directions. We point to a number of areas that have benefited from the interdisciplinary perspective and a focus on interactions between disciplines including: engineering curriculum; mechatronics research; control of nonlinear mechanical systems; real time control systems modelling; and time varying control systems